Contact Lens Versus Non–Contact Lens–Related Corneal Ulcers at an Academic Center. Issue 5 (September 2019) - Bennett, Lisa; Y. Hsu, Hugo; Tai, Shannon; Ernst, Benjamin; Schmidt, Eric J.; Parihar, Rohit; Horwood, Chelsea; Edelstein, Sean L.
Abstract : Purpose: To compare the infectious contact lens–related corneal ulcer (CLRU) and non-CLRU cases at Saint Louis University. Methods: Retrospective review of corneal ulcer cases identified by search of the ophthalmology and microbiology department databases between 1999 and 2016. Results: Six hundred seventy-seven cases of corneal ulcers were identified, of which 46% were CLRU. CLRU cases were seen more commonly in younger patients ( P <0.001) and women ( P =0.03) than non-CLRU cases. Many of the infections were vision-threatening as defined by central/paracentral location (73% CLRU and 71% non-CLRU [ P =0.60]) and large size of ulcer >2 mm 2 in 36% CLRU and 51% non-CLRU ( P =0.002). Causative pathogen in cultured CLRU was predominately Pseudomonas species (44%, P <0.001 vs. the non-CLRU group), other gram-negative (6%), gram-positive (33%), fungi (13%), and Acanthamoeba (5%). Comparatively, cultured non-CLRU was predominately gram-positive (64%, P <0.001 vs. the CLRU group), gram-negative (26%), and fungi (11%). The combined oxacillin-resistant Staphylococcus aureus and coagulase-negative Staphylococcus isolates were 35% and 34%, respectively. Despite the progressive increase in the number of corneal ulcers seen, the annual trend for any one particular organism for either CLRU cases or non-CLRU cases did not change significantly. Conclusions: Most of the cases were non-CLRU. CLRU was disproportionately associated with Pseudomonas species and non-CLRU with Staphylococcal species. Fungal infections were predominately caused by filamentous organisms in both groups. Acanthamoeba keratitis was exclusively associated with CL use.